2010
DOI: 10.1159/000277763
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Necrosis of the Bladder with Hypostatic Abscess: A Late Complication after Radiotherapy

Abstract: Background: Late urological complications after radiotherapy of a primary tumor in the pelvis are rare but challenging. We report a case of extensive bladder necrosis with hydronephrosis and sepsis nearly 45 years after radiotherapy. Case Report: An 80-year-old woman with infected hydronephrosis and with a history of radiotherapy due to cervical carcinoma was treated with JJ stenting. Due to the absence of any improvement, we performed a computed tomography which showed bilateral hypostatic abscesses in both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Severe complications are extremely rare and can have a notoriously long latency period, for example bladder rupture and fistula formation. [ 14 ] Pandey et al [ 15 ] reported a case of extensive bladder necrosis with hydronephrosis and sepsis nearly 45 years after radiotherapy. Fortunately, after treatment, the patient recovered 6 months later with completely healed wounds and nearly normal renal parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Severe complications are extremely rare and can have a notoriously long latency period, for example bladder rupture and fistula formation. [ 14 ] Pandey et al [ 15 ] reported a case of extensive bladder necrosis with hydronephrosis and sepsis nearly 45 years after radiotherapy. Fortunately, after treatment, the patient recovered 6 months later with completely healed wounds and nearly normal renal parameters.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Bladder necrosis has also been reported following hydrodistention, radiation exposure, infection, carcinoma, or iatrogenic damage to the bladder vascular supply. [10111213]…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, there must be partial necrosis of the bladder mucosa, sparing the detrusor, to allow regeneration of the mucosa. otherwise, bladder reconstruction is the only alternative, which was not feasible for our patient given the septic conditions and fragility of the bladder wall post radiation [15]. Hyperbaric oxygen has also been used as an adjunct to surgery and antibiotics helping to heal and regenerate tissues after debridement, improve vascularization and reduce bacterial colonization [8] [15].…”
Section: Discussionmentioning
confidence: 99%